Aleitamento materno entre usuárias da rede pública de saúde em município da região Sul do Brasil - Demitto, Marcela de Oliveira (2011)
A descriptive and exploratory study with quantitative approach with the objective of analyzing the practice of exclusive breastfeeding (EBF) among users of public health services of Maringá, Paraná State. The sample was composed by 378 women that accomplished prenatal care in one of the Basic Health Units of the municipal district, in 2009. Data collection was carried out from October 2010 to March 2011, through interviews using a structured questionnaire. For data analysis the stepwise procedure was used in models of logistic regression and mean tests through the analysis of parametric variance (ANOVA) and multiple comparisons of Tukey. The results were presented in three scientific articles. In the first one it was searched to analyze the prevalence of EBF and to identify the decisive factors of breastfeeding in the first six months of life. The prevalence of EBF in babies under six months of age was of 30.03%. Among the analyzed decisive factors on EBF only the marital status was statistically significant, revealing that the women who have a companion presented twice more chances of breastfeeding exclusively for six months than those that do not have one. In the second, it was investigated if women were informed regarding breastfeeding during prenatal and puerperium and if there was an association between the information and the presence of early difficulties in nursing. The importance of mother's milk and questions on babies positioning at breast and latch on reflex were the orientations mostly mentioned at the prenatal and maternity groups, respectively. The participation in pregnant women groups presented statistically significant association with the variable presence of difficulties on breastfeeding, revealing that the mothers who took part in these groups had twice less chances of presenting early difficulties to breastfeed their babies than those that did not take part in the groups. In the third article the objective was to identify the relationship between the introduction of a pacifier and the time of exclusive breastfeeding (EBF). More than half of the children did not make use of pacifier and among the ones that used; most of them began in the first month of life. No statistically significant difference was found between the age the pacifier was introduced and the duration of EBF. However significant statistical relationship was verified between the time of EBF and the use of pacifier. Thus, the children that did not make use of pacifier were exclusively breastfed for a longer period of time than the ones that made use of it. It was concluded that the prevalence of EBF is beneath the expectations of the World Health Organization, showing the need to review and reorganize the pro-breastfeeding actions among the population, especially among the women without companion. The importance of orientation on breastfeeding during prenatal period is confirmed, using the strategy of pregnancy groups. The use of pacifier should be seen, by the health professionals, as a sign of alert on the interruption of EBF. Concluding, the study revealed important aspects regarding duration of EBF that can contribute to follow health actions and to the elaboration of new strategies on breastfeeding in the municipal public health services.